Persepsi Petani Plasma Terhadap Pentingnya Peran Penyuluhan Perkebunan Kelapa Sawit di Desa Sari Galuh Kecamatan Tapung Kabupaten Kampar - Kartini Fitriyani; Cepriadi '; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this researchare : (1) to determine the organizing of extension oil palm plantation in Sari Galuh Village Tapung Sub-District of Kampar. (2) to determineThe Nucleus Estate Smallholder (NES) farmers perceptions about the importance the role of extension on oil palm plantations. Research method was survey, while 48 farmers were itnterviewed as respondent, in term of analysis, Scale Likert's Summated Rating (SLR) was used to answer the objective of this research. The resultshowed that organizing of extension has been running well according the element of extension.The NES farmers perceive that the role of extension is quite important to be implemented, it can be seen from : (1)Facility process study atquite important category; (2)Amenity access atquite important category; (3)Ability of leadership atquite important category;(4)Developing organizational atquite important category;(5)Analysing and solving problem at important category;(6) Developing awareness at important category;(7)Institutionalizing cultural values atquite important category;(8)Supervision or construction at quite important category;(9)Evaluation atquite important category. Keywords:Perception, The Nucleus Estate Smallholder (NES) farmers, roleof extension, oil palm plantation.